The Peacock’s Arrival in Greece and Rome, or How an Exotic Animal Became an Eschatological Symbol - Álvarez-Pedrosa, Juan Antonio (Anabasis. Studia Classica et Orientalia, 2019)
The Greeks knew of the peacock in the classical period from the Achaemenid Empire, a world in which it was associated with the monarchy and was reared in royal parks in the empire’s capital cities. Peacocks were introduced into Greece via two routes, and this influenced the different symbolic values attributed to the bird. On the one hand, it arrived in Athens as a personal gift from Artaxerxes I to the ambassadors who had led a diplomatic mission to the Achaemenid courts. Here, due to the price they commanded, peacocks rapidly became associated with ostentatious extravagance, political corruption, and the suspicion of medism. However, because the Athenians also attributed Iranian priests with privileged knowledge of the afterlife and the rituals associated with individual eschatology, the peacock also became associated with the destiny of man after death. The other place where the peacock was introduced was the island of Samos. Here, it quickly became associated with the island’s most famous son, Pythagoras, and consequently with his doctrine of reincarnation. As a symbol of reincarnation the peacock arrived in Rome. Subsequently, in the Imperial Roman period, pagans, Jews, and Christians alike adopted the peacock as a symbol of belief in a life hereafter.